Genetic variants in calcium regulatory cardiac genes and their contribution to Takotsubo syndrome. (25th November 2020) - Treu, F; Dybkova, N; Jung, P; Li, Y; Huebscher, D; Maurer, W; Hasenfuss, G; Voigt, N; Sossalla, S; Wollnik, B; Streckfuss-Boemeke, K
Abstract: Background and purpose: Takotsubo syndrome (TTS) is characterized by an acute left ventricular dysfunction similar to a myocardial infarction (MI) in the absence of coronary artery stenosis. Patients show symptoms similar to the acute MI with increased biomarkers and blood serum catecholamines. Recently, we developed a patient-specific TTS stem cell model and identified a higher sensitivity to catecholamine-induced stress. Furthermore, familial TTS cases and genetic studies point to a genetic predisposition. The purpose of this study was to analyze a genetic predisposition by characterizing genetic variants in genes associated with cardiac pathologies and their impact on calcium homoeostasis in TTS. Methods and results: Whole exome sequencing analysis of a TTS patient discovered 2 missense AHNAK variants in its C-terminal domain and in addition the missense variant F189L in the calcium buffering calsequestrin 2 gene (CASQ2). AHNAK is a 700kDa big nucleoprotein and is involved in the β-adrenergic regulation of the cardiac calcium channel Cav1.2. 3-month old TTS-iPSC-derived cardiomyocytes (CM) were generated and the variants were confirmed by sequencing. We found AHNAK higher expressed in TTS-iPSC-CMs compared to control, whereas no expression alteration was observed for Cav1.2. Since AHNAK is described to act as a repressor towards Cav1.2, which is relieved under β-adrenergic stimulation, we analyzed the effect of AHNAK variants on a potential co-localization and interaction between both proteins. AHNAK and Cav1.2 were shown to co-localize in the cytoplasm as well as the membranes and co-immunoprecipitation experiments confirmed an interaction of AHNAK and Cav1.2 in all tested control- and TTS-iPSC-CMs. On a functional level, we were able to show by patch clamp analysis that Cav1.2 calcium currents are significantly increased in TTS-iPSC-CMs compared to control. The influence of CASQ2-F189L on sarcomeric reticulum (SR) calcium load was analyzed by epifluorescence microscopy using FURA4 and caffeine-applications. We found significantly decreased SR calcium content with an increased fractional release during systole in TTS-iPSC-CMs. To test, whether these variants are the main reason for altered interaction of AHNAK and Cav1.2, calcium currents or SR calcium load in TTS need to be proven in the future by using CRISPR/Cas9-rescued AHNAK/CASQ2 lines. Conclusion: Here we show the cardiac functional consequences of AHNAK and CASQ2 missense mutations in TTS-iPSC-CMs with regard to calcium currents and SR calcium load. These results show that AHNAK and CASQ2 variants may predispose to TTS and enable a new therapeutic option for TTS. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Else Kröner-Fresenius Foundation